Rhythm analysis and charging during chest compressions reduces compression pause time. (May 2015) - Partridge, R.; Tan, Q.; Silver, A.; Riley, M.; Geheb, F.; Raymond, R.
Abstract: Purpose: Prolonged chest compression interruptions immediately preceding and following a defibrillation shock reduce shock success and survival after cardiac arrest. We tested the hypothesis that compression pauses would be shorter using an AED equipped with a new Analysis during Compressions with Fast Reconfirmation (ADC-FR) technology, which features automated rhythm analysis and charging during compressions with brief reconfirmation analysis during compression pause, compared with standard AED mode. Methods: BLS-certified emergency medical technicians (EMTs) worked in pairs and performed two trials of simulated cardiac resuscitation with a chest compression sensing X Series defibrillator (ZOLL Medical). Each pair was randomized to perform a trial of eight 2-min compression intervals (randomly assigned to receive four shockable and four non-shockable rhythms) with the defibrillator in standard AED mode and another trial in ADC-FR mode. Subjects were advised to follow defibrillator prompts, defibrillate if "shock advised, " and switch compressors every two intervals. Compression quality data were reviewed using RescueNet Code Review (ZOLL Medical) and analyzed using paired t -tests. Results: Thirty-two EMT-basic prehospital providers (59% male; median 25 years age [IQR 22–27]) participated in the study. End of interval compression interruptions were significantly reduced with ADC-FR vs. AED mode ( p  < 0.001). For shockable rhythms, pre-shock pause was reduced significantly with ADC-FR compared with AED use (7.35 ± 0.16 s vs. 12.0 ± 0.22 s, p  < 0.001) whereas post-shock pause was similar (2.08 ± 0.14 s vs. 1.77 ± 0.14 s, p  = 0.1). Conclusion: Chest compression interruptions associated with rhythm analysis and charging are reduced with use of a novel defibrillator technology, ADC-FR, which features automated rhythm analysis and charging during compressions.